1987
DOI: 10.1042/bj2450583
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phosphorylated 3-deoxy-manno-octulosonic acid as a component of Haemophilus influenzae lipopolysaccharide

Abstract: A phosphorylated 3-deoxy-manno-octulosonic acid (KDO) was released from the lipopolysaccharide (LPS) of the deep rough mutant (Rb+I69) of Haemophilus influenzae by acid hydrolysis. Both phosphorylated and dephosphorylated KDO, produced by treatment with alkaline phosphatase, were identified by gas chromatography-mass spectrometry after trimethylsilylation. This technique provides a rapid and reliable method for the identification of phosphorylated KDO in LPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…If KDO is detected in the extracellular culture fluid, respcctively. Activity phosphorylated, it does not react efficiently in the thiobarbituof the chloride-stimulated cellobiosidase was mainly found in ric acid assay (61), but because of obviously interfering subthe extracellular culture fluid. The ratio of the enzyme activity stances, this marker was not pursued further.…”
Section: Resultsmentioning
confidence: 99%
“…If KDO is detected in the extracellular culture fluid, respcctively. Activity phosphorylated, it does not react efficiently in the thiobarbituof the chloride-stimulated cellobiosidase was mainly found in ric acid assay (61), but because of obviously interfering subthe extracellular culture fluid. The ratio of the enzyme activity stances, this marker was not pursued further.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylated sugars were determined indirectly by recording the increase of GC peak area after dephosphorylation of samples with aqueous 48 YO (w/w) hydrofluoric acid at 4 "C for 72 h (Sonesson e t al., 1989a). Phosphorylated sugars were also detected by HPAEC-PED, ASA and by GC analysis of trimethylsilyl (TMS) derivatized methyl glycosides (Zamze et al , 1987). Absolute configurations of the sugars were determined by GC analysis of 2-(R)-butyl and 2-(S)-butyl glycoside diastereomeric derivatives (Gerwig e t al., 1978) after TFA derivatization and retention time comparison to authentic standards.…”
Section: Methodsmentioning
confidence: 99%
“…þ and the wild-type strain RM7004 were cultivated as described by Zamze et al (1987). Bacteria were washed with ethanol, acetone (twice), and ether, and dried.…”
Section: Bacteria and Bacterial Lps H Influenzae I-69 Rdmentioning
confidence: 99%
“…influenzae LPS consists of an oligosaccharide (Phillips et al, 1993), with a general architecture similar to that in the intensively studied enterobacteria (Holst and Brade, 1992), linked to the lipid A moiety via a phosphorylated 3-deoxy-D-manno-octulopyranosonic acid (Kdo) residue. Studies on the H. influenzae mutant strain I-69 Rd ¹ /b þ (hereafter referred to as I-69) revealed that it contained a truncated LPS composed of lipid A and a single phosphorylated Kdo residue (Zamze et al, 1987). I-69 was identified from a genomic library of chromosomal DNA in a lambda vector when it was observed that transformants using DNA from one of the lambda clones produced an opaque phenotype (Zwahlen et al, 1985).…”
Section: Introductionmentioning
confidence: 99%